The literary education guideline in the National Literacy Policy: counterpoints (Práxis Educativa, 2020)
This paper, anchored in the enunciative-discursive Bakhtinian perspective of language, aims to reflect how the guideline of literary education is approached in the National Literacy Policy (Política Nacional de Alfabetização - PNA) and to what extent it is configured as a conception related to the neoliberal ideology that manages its implementation. Based on a documental analysis, the focus is on the “Caderno da PNA” (PNA Guideline booklet), made official in 2019. In this text, it is considered that this is a government policy, marked by the upsurge in social inequality, retrogression and ultraconservatism, which rejects the inherent public democracy debate and hurts the critical dimension of literacy. It concludes that its guideline is based on a neoliberal public policy that weakens the possibility of a critical literary education and, thus, deprives, especially subjects in the process of literacy, of an inalienable right: Literature.Keywords: Literary education. Educational public policies. PNA.